NATO 2022 Strategic Concept in the Face of Security Threats - Olbrycht, Paweł (Historia i Polityka, 2026)
This study aimed to explore the strategic assumptions contained in the NATO 2022 Strategic Concept. The research process used literature sources on NATO strategic concepts and strategic documents in the form of the NATO 2022 Strategic Concept. Qualitative research methods were applied, which included the following: to find out the results of the research conducted so far on the issue in question, literature research and a comparative analysis were carried out to compare NATO’s strategic assumptions, as included in the 2022 NATO Strategic Concept and previously applicable NATO 2010 Strategic Concept. The comparison of the documents showed a significant difference in the strategic assumptions of the NATO expressed in the content of the NATO 2010 Strategic Concept and the NATO 2022 Strategic Concept, determined primarily by the change in NATO’s attitude towards the Russian Federation (from a partner to a source of threat) and the change in the assessment of the security of the Euro-Atlantic area (from stable to unstable). The further evolution of NATO’s strategic assumptions will depend primarily on the actions of the Russian Federation, including in the context of its armed invasion of Ukraine.